Development of an Android Mobile Application for Capital Market Education A Case Study at KSPM UTY - Eusebia Nawang Ari; Muhammad Zakariyah (Kirana Publisher (KNPub), 2024)
This study explores the development of an Android mobile application to enhance capital market education within the Capital Market Study Group (KSPM) at Yogyakarta Technology University (UTY). The application aims to provide members with accessible and structured learning resources, including downloadable materials, interactive quizzes, and discussion forums. The system defines three main user roles that is: members, management, and super admin. Members can see and download capital market materials and quizzes to evaluate their understanding, while management oversees manage of capital market materials. The super admin role is responsible for overall user management and monitoring bug reports. The system utilizes Firebase as its database to enable real-time data management and synchronization, ensuring reliability. The implementation of this application has demonstrated its effectiveness in fostering better understanding of capital market concepts among KSPM members. This development represents a significant step toward more interactive and efficient learning methods, contributing to advancements in educational technology.